2009
DOI: 10.1016/j.jfms.2008.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and innate immunity in feline patients with diabetes mellitus: The role of nutrition

Abstract: This study was undertaken to test the hypothesis that oxidative stress is increased and neutrophil function is decreased in cats with diabetes mellitus (DM). Measures of oxidative stress and neutrophil function were evaluated in 20 control and 15 diabetic cats. Cats were then fed a diet designed specifically for feline diabetics (Purina DM Dietetic Management Feline Formula) for 8 weeks, after which all assays were repeated. Cats with DM had significantly less plasma superoxide dismutase (SOD) than control cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…Hence, the increased concentrations of membrane carbonyls and decreased concentrations of cytoplasmic thiols in the erythrocytes of diabetic cats in the present study clearly suggests that oxidative stress occurs in untreated diabetic cats at the time of diagnosis, similar to findings in humans with type 1 and type 2 DM . It is difficult to explain why differences were not evident in previous studies, particularly when diabetic cats were considerably older and had higher body weight . Aging and obesity in humans are associated with increased oxidative stress of erythrocytes, and thus differences would have been expected in older and heavier cats …”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Hence, the increased concentrations of membrane carbonyls and decreased concentrations of cytoplasmic thiols in the erythrocytes of diabetic cats in the present study clearly suggests that oxidative stress occurs in untreated diabetic cats at the time of diagnosis, similar to findings in humans with type 1 and type 2 DM . It is difficult to explain why differences were not evident in previous studies, particularly when diabetic cats were considerably older and had higher body weight . Aging and obesity in humans are associated with increased oxidative stress of erythrocytes, and thus differences would have been expected in older and heavier cats …”
Section: Discussionsupporting
confidence: 54%
“…To date, there are limited data substantiating the presence of oxidative stress in diabetic cats . In the present study, erythrocytes of newly diagnosed diabetic cats had higher concentrations of membrane carbonyls and lower levels of cytoplasmic TBAR and thiols compared with well‐matched healthy controls.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…A study of glutathione and glutathione-related enzymes in patients on maintenance dialysis found that plasma GPx activity was significantly lower in the dialysis group than in the healthy control group (Ahmadpoor et al 2009). A study of oxidative stress in cats with diabetes mellitus (DM) also reported that plasma GPx levels in the DM cats were lower than in the control cats (Webb and Falkowski 2009 Fig. 4 Regression analysis between creatinine and GSH/ GSSG ratio in the clinically normal cats (dark blue) and CKD cats (blue).…”
Section: Discussionmentioning
confidence: 99%
“…In this situation the organism is unable to detoxify reactive oxygen species, which accumulate, producing a harmful effect on the functional and structural integrity of biological tissues (Yilmaz, 2012). Cats seem to be more susceptible to oxidative stress and damage, probably influenced by the particular spleen structure of this species (Christopher et al, 1995;Harvey and Kaneko, 1977), and a situation of oxidative stress has been demonstrated in various diseases in this species such as diabetes mellitus (Webb and Falkowski, 2009), chronic renal failure (Keegan and Webb, 2010) and feline immunodeficiency virus (FIV) infection (Webb et al, 2008). However, to the author's knowledge there are no studies about oxidative stress in feline infectious peritonitis (FIP), a viral disease resulting from feline coronavirus (FCoV) infection.…”
Section: Introductionmentioning
confidence: 99%